PENGEMBANGAN BAHAN AJAR BERBASIS CERITA RAKYAT KEARIFAN LOKAL UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PEMBELAJARAN BUDAYA MELAYU RIAU KELAS III SDN 36 BATHIN SOLAPAN - Adinda Febriany Br. Sembiring; Umar Darwis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The problem in this research is the lack of student interest in the Malay Arabic learning process. The aim of this research is to determine the development of teaching materials based on local wisdom folklore to increase students' interest in learning in Riau Malay culture subjects for class III SDN 36 Bathin Solapan. This type of research is Research and Development (R&D) with an ADDIE design (analysis, design, development, implementation and evaluation). The research subjects for developing teaching materials based on local wisdom folklore in the Riau Malay Culture subject in class III are material experts, language experts, and design experts. The object of this research is folklore-based teaching materials on the subject of Riau Malay Culture. This development research was carried out in the even semester in class III of SD 36 Bathin Solapan. The level of validity and suitability of teaching materials is known through the results of analysis of product testing activities carried out through material expert validation, language expert validation, and design expert validation. Data collection techniques are observation, documentation, questionnaires. The data analysis technique used is feasibility testing and validity testing of teaching materials obtained from material, design and language expert validators as well as teacher responses. Based on the results of presentations from material experts, language experts, design experts and the teacher's responses, the average was then calculated and obtained 88.75 percentages were converted into a feasibility qualification table and included in the category as very suitable/very valid for use in the learning process, with The existence of these teaching materials makes the learning process more conducive and enjoyable. Then it can make it easier for educators to create interesting and creative teaching materials. Helping in conveying the legends of Riau Malay cultural folklore.